Competition and globalisation in economic sciences. Selected aspects - Gorynia, Marian (Economics and Business Review, 2019)
The aim of the paper is to identify and assess the role of economic sciences inrelation to competitiveness and globalisation, two basic concepts of the market economy.This role is to explain and interpret their essence but also to determine their potentialpractical usefulness, primarily in the context of economic policy development.The considerations mentioned in the article are, as a rule, of a general and universalnature and do not relate especially to any particular countries or groups of countries.The basic method employed in the study is a critical analysis of the subject literature.The paper consists of an introduction, three sections, and conclusions. Section 1 containsa basic discussion of the subject of economic sciences and describes their fourfeatures: cognitive productivity, practical usefulness, dismal nature and beauty. Section2 presents the contribution of economic sciences to understanding and interpretingthe phenomenon of competitiveness. Section 3 focuses on defining and elucidating theidea of globalisation and an examination of its most important aspects. The paper endswith eight conclusions formulated on the basis of this discussion.